La relación entre el crimen y el turismo para el caso peruano (1997-2019) - Camacho Leandro, Mariana Angelica (2022)
This research is an analysis of the relationship between crime and tourism in Peru based on the Regional Information System for Decision Making (2021). The panel VAR econometric model and the Granger causality Test allow demonstrating the relationship and causality between tourism and crime in Peru, using the bed occupancy rate by department as the proxy variable of tourism and the number of people arrested for committing one crime per department as the proxy variable of crime in the period 1997-2019. It is concluded that there is a positive causal relationship between tourism and crime, that is, more tourism, more crime.